Metaphors: Universal, specific, and public - Nirmala, Deli (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2011)
Metaphors in written discourse, such as letters using bahasa Indonesia, can be derived from the metaphorical expressions used by writers to editors, showing conceptualization based on what they experience, feel, and think in their lives. This paper aims to find out the universality of the concepts shown by the metaphors and the users employing them. Using nonparticipant observation with a note-taking technique, the data are collected and selected purposively. Through distributional, referential, reflective introspective, and abductive inferential methods, the data are analyzed. The results indicate that metaphors can be grouped into universal, specific, and public types based on the universality and specificity of the concepts conveyed, as well as the users employing them. This implies that bahasa Indonesia conveys concepts similar to those of other languages in the world, which is influenced by experiences from different times and places encountered by Indonesians living in an agricultural country.